Evaluation of implementation 10 steps to successful breastfeeding program at Dukuh Klopo Community Health Center - Niken Grah Prihartanti; Diah Wijayanti Sutha (Science Midwifery, 2026)
Various regulations regarding programs that support breastfeeding already exist, but their coverage and other practices related to breastfeeding such as IMD have not reached the set targets, especially in Community Health Centers (Puskesmas) because so far the focus of implementation has only been on hospitals. The purpose of this study was to evaluate the implementation of the success of the 10 LMKM program at the Dukuh Klopo Community Health Center, Jombang. This research is a qualitative study with a case study research design. The data collection method used in-depth interviews. The sample in this study was 3 providers and 10 mothers who received the program. The place and time of the research were at the Dukuh Klopo Community Health Center from October to November 2025. The research analysis used the Miles and Hubberman model. The results showed that all midwives supported breastfeeding activities including discussions since pregnancy, all midwives assisted with early breastfeeding initiation (IMD) and joint care for mothers who gave birth. All breastfeeding mothers never received gifts that included the logo of a breast milk substitute (PASI) brand and mothers were sensitive to signs that their babies wanted to breastfeed. However, one aspect of the program remains incomplete: the lack of breastfeeding support groups (KP-ASI). A written policy regarding the 10 LMKMs is needed, and it is hoped that all midwives will participate in lactation management training to optimize their implementation.